Cold-rolled steel and method for producing the same

By controlling the chemical composition and processing technology of cold-rolled steel strip, the problem of producing high-strength cold-rolled steel strip with good local formability has been solved, achieving the effect of low cost, high strength and good formability, which is suitable for continuous annealing line production.

CN120548381BActive Publication Date: 2026-11-06VOESTALPINE STAHL GMBH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202480008219.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-01-18
Filing Date
2024-01-17
Publication Date
2026-11-06
Estimated Expiration
2044-01-17

Smart Images

  • Figure CN120548381B_ABST
    Figure CN120548381B_ABST
Patent Text Reader

Abstract

This invention relates to a cold-rolled steel strip or sheet, comprising 0.02-0.10 C, 0.05-0.5 Si, 0.6-1.0 Mn, 0.015-1.5 Al, 0.03-0.12 Ti, and 0.01-0.06 Nb, wherein Ti+Nb is 0.05-0.15. The yield strength (R) of the strip or sheet is... p0.2 The tensile strength is 800-950 MPa, and the tensile strength (R) is 800-950 MPa. m The pressure is 830-1000 MPa, and the total elongation (A) is... 80 Ferrite ≥ 95%, and porosity (λ) ≥ 60%. The microstructure, by volume %, consists of: ferrite ≥ 95%, and pearlite, cementite, carbides, nitrides, and / or carbonitrides ≤ 5%. Flexibility (Ri / t) ≤ 1.0. This invention also relates to a continuous method for producing strips or sheets.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a cold-rolled strip or sheet having high strength and good local formability. The invention also relates to a continuous annealing method for producing the strip or sheet. Background Technology

[0002] The development of materials combining high strength and formability contributes to weight reduction in automotive applications. This development involves improving formability without reducing the strength of cold-rolled steel sheets used for general purposes, and increasing strength while maintaining the formability of various high-strength steel sheets.

[0003] For some components, good local formability is particularly desirable, such as hole expansion and bending. Seat rails are an example of components requiring high yield strength and good bendability. For other components, hole expansion may be more important. Cost is also a significant factor.

[0004] Typically, the seat is formed from high-strength microalloyed steel strip, which is produced on a production line using a reversible cold rolling mill and batch annealing of cold-rolled strip. This steel strip is smaller in size than that produced on a continuous cold rolling mill and continuous annealing line. The strip is usually uncoated.

[0005] For wider strips, batch annealing is also a common annealing method, but it is usually used for steel grades with lower strength. For higher strength grades, continuous annealing lines are typically used.

[0006] WO 2022 / 1845780 A1 discloses a cold-rolled steel product with a ferritic microstructure. The steel is alloyed with at least one element from the Ti, Nb, V group and at least one element from the Cr, Mo, W group. The use of expensive alloying elements can lead to higher product costs. It is cold-worked to a reduction degree of 5-70% and continuously annealed at a temperature in the range of 700-900°C.

[0007] CN112680655A discloses the yield strength (R) p0.2 This is a cold-rolled steel product with a strength of 700-850 MPa. The steel is microalloyed with Ti and Nb. The amount of Mn is 1.0-1.5%, preferably 1.2-1.4%. It is cold-worked to a reduction of 60-70% and continuously annealed at a temperature in the range of 770-800°C. After annealing, the product is slowly cooled to a temperature of 630-670°C, then rapidly cooled to 400-450°C, where it is overaged. The microstructure consists of austenite.

[0008] EP1399598B2 discloses a cold-rolled steel product. The steel is alloyed with at least one element from the Ti, Nb, and V groups. It is cold-worked to a reduction of 5-20%, particularly 5-10%, and annealed at a temperature in the range of 450-700°C, preferably 550-650°C. Mn and Cr are high in all embodiments.

[0009] CN109207842A discloses a cold-rolled steel product. This steel is microalloyed with Ti and Nb. The amount of Mn is 1.1-1.5%, preferably 1.2-1.5%, to ensure the strength of the steel. It is cold-worked to a reduction of 40-60%, preferably 45-50%.

[0010] It would be advantageous to provide improved wide steel strip and methods for producing it, which can be used for components requiring high yield strength and good local formability (e.g., expansion ratio and bendability). The steel strip should preferably be capable of low-cost, high-volume production in a continuous annealing line. Furthermore, process stability is a desirable outcome to minimize losses due to discarding substandard products. It should preferably be easy to weld. Detailed Implementation

[0011] The invention is described in the claims.

[0012] In a preferred embodiment, the cold-rolled steel strip or sheet has a composition consisting of the following alloying elements (in weight %):

[0013] C0.02–0.10

[0014] Si 0.05–0.5

[0015] Mn0.6–1.0

[0016] Al 0.015–1.5

[0017] Ti 0.03–0.12

[0018] Nb 0.01–0.06

[0019] Ti+Nb0.05–0.15

[0020] The balance consists of iron and impurities, and the impurity elements are limited to...

[0021] V≤0.10

[0022] Cr≤0.10

[0023] Mo≤0.05

[0024] W≤0.05

[0025] Ni≤0.20

[0026] Cu≤0.20

[0027] Sn≤0.015

[0028] Zr≤0.010

[0029] As≤0.010B≤0.001

[0030] Ca≤0.05

[0031] P≤0.02

[0032] S≤0.005

[0033] N≤0.05

[0034] O≤0.0003

[0035] H≤0.0020

[0036] The importance of individual elements and their interactions with each other, as well as the limitations on the chemical composition of the claimed alloy, are briefly explained below. Throughout the specification, all percentages of the chemical composition of the steel are given in weight % (wt.%). Throughout the specification, microstructural composition is expressed in volume % (vol.%). The upper and lower limits of the individual elements can be freely combined within the limits listed in the claims. For all values ​​given in this application, the arithmetic precision of the numerical values ​​may be increased by one or two digits. Thus, a value given as, for example, 0.1% can also be expressed as 0.10 or 0.100%.

[0037] C: 0.02-0.10%

[0038] Carbon (C) is important for achieving the desired strength level. When C is below 0.02%, it is difficult to obtain a tensile strength of 830 MPa. If the C content is too high, undesirable high amounts of phases, such as pearlite and / or cementite, can form. These phases can impair the ductility of the steel of the present invention, and particularly its localized formability. Therefore, an upper limit is set at 0.10%. The upper limit can be further limited to 0.09%, 0.08%, or 0.07%. The lower limit can be further limited to 0.03% or 0.04%. The preferred range is 0.03-0.07%.

[0039] Si: 0.05-0.5%

[0040] Si is a ferrite-forming element, which provides solid solution strengthening and can be used for deoxidation of molten steel. The addition of Si can also inhibit the precipitation of pearlite and cementite. Excessive Si content can impair the surface quality of steel sheets and adversely affect coating properties. When Si levels are too high, welding can also be impaired due to liquid metal embrittlement (LME) caused by excessive Si addition. The lower limit is 0.05%, and it can be 0.10%, 0.15%, 0.20%, or 0.25%. The upper limit is 0.5%, and it can be 0.45%, 0.40%, or 0.35%. The preferred range is 0.20-0.40%.

[0041] Mn: 0.6-1.0%

[0042] Manganese is a solid solution strengthening element in ferrite. Mn lowers the Ac3 temperature. Excessive Mn can stabilize austenite and prevent the formation of ferrite and pearlite from austenite during cooling. Mn is also an expensive element and is therefore limited. The upper limit is 1.0%, and it can be 0.99%, 0.98%, 0.97%, 0.96%, or 0.95%. The lower limit is 0.6%, and it can be 0.7% or 0.8%. The preferred range is 0.7-1.0%, more preferably 0.8-1.0%.

[0043] Al: 0.015-1.5%

[0044] Al is an alloying element that raises the Ac3 temperature, promotes ferrite formation, and facilitates precipitation hardening. This steel does not require the intentional addition of Al as an alloying element. However, Al is commonly used as a deoxidizer in molten steel, so even if not intentionally added as an alloying element, Al will be present in small amounts. Therefore, a lower limit is set at 0.015%. Upper limits can be limited to 1.0%, 0.9%, 0.8%, 0.7%, 0.6%, 0.5%, 0.4%, 0.3%, 0.2%, or 0.1%.

[0045] Ti: 0.03-0.12%

[0046] This steel is microalloyed with titanium. Ti is a strong nitrogen and deoxidizer, and TiN forms in the billet at high temperatures. Due to the precipitation hardening effect and its influence on the reduced grain size, TiC and Ti(C,N) precipitate at lower temperatures, improving strength and toughness. Another property of Ti is the delay or inhibition of recrystallization. This can be achieved through dissolved elements as well as the precipitation of carbides and carbonitrides. The beneficial effect of Ti tends to saturate above 0.12%. The lower limit is 0.03%, and it can be 0.04%, 0.05%, 0.06%, 0.07%, or 0.08%. The upper limit is 0.12%, and it can be 0.11% or 0.10%. The preferred range is 0.07-0.11%.

[0047] Nb: 0.01-0.06%

[0048] This steel is microalloyed with Nb. Nb is used to improve strength and toughness due to its effect on grain size. Nb increases the strength of the steel and reduces the size of the ferrite grains due to the precipitation of NbC and / or Nb(C,N) in the ferrite matrix. Another property of Nb is the delay or inhibition of recrystallization. This can be achieved through dissolved elements and the precipitation of carbonitrides. The lower limit is 0.01%, and it can be 0.02%. The upper limit is 0.06%, and it can be 0.05%. The preferred range is 0.02-0.05%.

[0049] Ti+Nb: 0.05-0.15%

[0050] To ensure sufficient strength of the steel, the combined Ti+Nb content should be at least 0.05%. The lower limit is 0.05%, and it can be 0.06%, 0.07%, 0.08%, 0.09%, or 0.10%. The upper limit is 0.15%, and it can be 0.14% or 0.13%. The preferred range is 0.08-0.14%.

[0051] V: ≤0.10%

[0052] V functions similarly to Nb because it contributes to precipitation hardening and grain refinement. Another property of V is the delay or inhibition of recrystallization. This can be achieved through dissolved elements and the precipitation of carbonitrides. Steel may contain ≤0.10% V. According to the invention, the intentional addition of V is not required. The upper limit is limited to 0.10%, and may be limited to 0.05%, 0.03%, or 0.01%. The lower limit may be 0.001%.

[0053] Cr: ≤0.10%

[0054] This steel does not require Cr. Cr is effective in increasing the strength of steel sheets. Cr is an element that forms ferrite and delays the formation of pearlite and bainite. However, Cr is an expensive element and is therefore not intentionally added. However, Cr can exist as an impurity, for example, from scrap treatment. The upper limit is limited to 0.10%, and can be limited to 0.09%, 0.08%, 0.07%, 0.06%, or 0.05%. The lower limit is 0.005%, and can be further increased to 0.01%.

[0055] Mo≤0.05%

[0056] Mo is a strengthening element. However, Mo is an expensive element. Therefore, it is undesirable to intentionally add Mo according to the present invention. Therefore, the upper limit is limited to 0.05%, and may be limited to 0.04%, 0.03%, 0.02%, or 0.01%. Mo may exist as an impurity, for example, from waste disposal. Therefore, the lower limit may be 0.0005%, and may be further increased to 0.001%.

[0057] W≤0.05%

[0058] W is a strengthening element. However, W is an expensive element. W can also complicate waste disposal. Therefore, it is not desirable to intentionally add W according to the present invention. Therefore, the upper limit is limited to 0.05%, and may be limited to 0.04%, 0.03%, 0.02%, or 0.01%.

[0059] Ni: ≤0.20%

[0060] Ni is an undesirable impurity element, which is limited to ≤0.20% by careful selection of the waste materials used. The upper limit can be further limited to 0.10% or 0.05%.

[0061] Cu: ≤0.20%

[0062] Cu is an undesirable impurity element, which is limited to ≤0.20% by careful selection of the waste materials used. The upper limit can be further limited to 0.10% or 0.05%.

[0063] Sn≤0.015%

[0064] Sn is an undesirable impurity element, which is limited to ≤0.015% by careful selection of the waste materials used. The upper limit can be further limited to 0.010% or 0.005%.

[0065] Zr≤0.010%

[0066] Zr is an undesirable impurity element, which is limited to ≤0.010% by careful selection of the waste materials used. The upper limit can be further limited to 0.05%.

[0067] As≤0.010%

[0068] As is an undesirable impurity element, which is limited to ≤0.010% by careful selection of the waste materials used. The upper limit can be further limited to 0.05%.

[0069] B: ≤0.001%

[0070] B is an undesirable impurity element, which is limited to ≤0.001% by careful selection of the waste materials used. B above this level adversely affects flexibility. The addition of B makes waste recycling more difficult and can also degrade processability.

[0071] Ca≤0.05

[0072] Ca can be used to modify non-metallic inclusions. The upper limit is 0.05%, and it can be set to 0.04%, 0.03%, or 0.01%. According to the invention, the intentional addition of Ca is not necessary. Therefore, the upper limit can be limited to ≤0.005%.

[0073] Other impurity elements are included in the steel in amounts that can be present normally.

[0074] It is also preferable to control the nitrogen content so that N: ≤0.05%, preferably ≤0.01%. The preferred range is 0.001-0.008%. Within this range, stable nitrogen fixation can be achieved.

[0075] Oxygen and hydrogen are limited to

[0076] O: ≤0.0003

[0077] H: ≤0.0020

[0078] Phosphorus and sulfur are limited to

[0079] P: ≤0.02

[0080] S: ≤0.005

[0081] Carbon equivalent is expressed as C Eq =C+Mn / 6+(Cu+Ni) / 15+(Cr+Mo+V) / 5.

[0082] Typically, the carbon equivalent C has been assessed. Eq Up to 0.45% results in good weldability; otherwise, heat treatment is required to protect the steel from martensitic cracking. However, even lower C... Eq This can further improve weldability. Therefore, C Eq The preferred upper limit is set at 0.28. This also reduces costs, as these alloying elements are expensive.

[0083] The steel is preferably recovered annealed with less than 20% by volume recrystallized grains. The microstructure is ferrite and contains ≥95% ferrite and ≤5% pearlite, cementite, carbides, nitrides and / or carbonitrides. The microstructure does not contain other phases, such as austenite, martensite or bainite.

[0084] The microstructure ratio can be obtained by cutting a sample from a steel plate and polishing the cross-section of the plate parallel to the rolling direction. Samples can be ground to 1 / 4 of the plate thickness for measurement. The surface can be etched to make the phases easier to identify. A scanning electron microscope (SEM) with 2000x magnification can be used to study the etched surface and determine the amount of phase.

[0085] The mechanical properties of the steel to be protected are important, and the following requirements must be met:

[0086] Yield strength (R) p0.2 800-950MPa

[0087] Tensile strength (R) m 830-1000MPa

[0088] Total elongation (A) 80 ≥9%, preferably ≥10%

[0089] Pore ​​expansion ratio (λ) ≥ 60%

[0090] It also satisfies the following mechanical properties:

[0091] Flexibility (Ri / t) ≤ 1.0

[0092] R m R p0.2 Value and total elongation (A) 80 The sample is obtained according to the industrial standard DIN EN ISO 6892-1, in which the sample is taken in the longitudinal direction of the strip.

[0093] The hole expansion ratio (λ) was determined according to ISO / WD 16630:2009(E) by a hole expansion test. In this test, a tapered punch with a 60° apex was pressed into a 10 mm diameter hole made in a 100 × 100 mm steel sheet. The test was stopped once the first crack was identified, and the hole diameter was measured in two mutually orthogonal directions. The arithmetic mean was used for calculation.

[0094] The porosity (λ), expressed as a percentage, is calculated as follows:

[0095] λ = (Dh - Do) / Do × 100

[0096] Where Do is the initial diameter of the hole (10mm), and Dh is the diameter of the hole after testing.

[0097] Flexibility is evaluated by the ratio of the ultimate bending radius (Ri) to the sheet thickness (t), whereby the ultimate bending radius (Ri) is defined as the minimum bending radius without cracking. For this purpose, the steel sheet is bent using a 90° V-block, according to JIS Z2248. The value obtained by dividing the ultimate bending radius by the thickness (Ri / t) should be less than or equal to 1.

[0098] The strip thickness can be 0.1-4 mm, preferably 0.2-3 mm. Under slitless conditions, the strip width can be 500-2000 mm, preferably 700-1750 mm.

[0099] The proposed steel strip can be produced by a method including the following steps:

[0100] a) Produce steel billets with the composition suggested above. The steel billets may be produced, for example, by converter smelting or in an electric arc furnace plant and secondary metallurgy to ultimately determine the composition.

[0101] b) Reheat the billet to 1200°C to 1300°C for 10-300 minutes. Set the time and temperature to allow the carbides and carbonitrides to completely dissolve.

[0102] c) The reheated billet is hot-rolled entirely within the austenitic range, with a final hot-rolling temperature in the range of 850-950°C, to obtain hot-rolled steel strip. The final hot-rolling temperature should be high enough to keep the microalloying elements Nb and Ti in a molten state.

[0103] d) Cool the hot-rolled strip to the coiling temperature. The cooling rate is typically about 5-100°C / s.

[0104] e) Subsequently, the hot-rolled strip is coiled at a coiling temperature in the range of 470-670°C. The coiling temperature can be modified to keep the microalloying elements Nb and Ti in a soluble state, or to use Nb and Ti as hardening precipitate-forming elements to promote precipitation hardening. The coiling temperature can be below 570°C to keep Nb and Ti in a soluble state and / or as very fine precipitates. For precipitation hardening effect, the coiling temperature can be above 570°C. Carbides and carbonitrides form during coiling after hot rolling or during final annealing and delay recrystallization in the final annealing step.

[0105] f) Optionally, the wound strip is subjected to a scale removal process, such as pickling. Preferably, the pickling acid is H2SO4 or HCl.

[0106] g) Subsequently, cold-roll the steel strip with a reduction in the range of 20-40%. The low reduction is to suppress recrystallization of the entire microstructure during the final annealing in step h). A preferred reduction is 25-35%. The upper limit of the reduction can be set to 40%, 39%, 38%, 37%, 36%, or 35%.

[0107] h) Final continuous annealing of cold-rolled strip at a temperature ranging from 700 to 800°C for 25 to 175 seconds. Final continuous annealing is a recovery annealing designed to remove and / or rearrange defects in the crystal structure of the cold-rolled material, and for precipitation hardening using Nb and Ti as the forming elements of the hardening precipitates. Due to the low temperature and duration, the recrystallization is very low. Final annealing can be performed on a continuous annealing line (CAL), a hot-dip galvanizing line (HDGL), or a continuous electroplating line (CEL).

[0108] i) The final annealed strip is cooled to an over-aging temperature between 200 and 500 °C at a cooling rate of 2–100 °C / s. Higher cooling rates minimize carbon diffusion to grain boundaries and the formation of grain boundary cementite. The lower limit can be further limited to 5 °C / s, 7.5 °C / s, 10 °C / s, or 15 °C / s. The upper limit can be further limited to 90 °C / s, 80 °C / s, 70 °C / s, 60 °C / s, or 50 °C / s. The cooling step may include initial slow gas jet cooling at a rate in the range of 2–20 °C / s, followed by rapid jet cooling at a rate in the range of 10–100 °C / s. Preferably, the rate is 20–80 °C / s.

[0109] j) Optionally, the strip that has been finally annealed is subjected to an aging period of 10 to 1000 seconds at 200°C to 500°C.

[0110] k) Optionally, the strip is leveled at a rolling elongation of 0-2%. The purpose of leveling is to impart the desired surface finish and straightness to the strip.

[0111] l) Optionally, the strip is coated with a zinc-based coating, preferably in a continuous galvanizing process.

[0112] m) Optionally, the strip material is cut into sheets.

[0113] Example 1

[0114] Steel billets are produced through conventional metallurgical processes, including converter smelting and secondary metallurgy. Apart from a balance of Fe and impurities, steel has the following elemental composition by weight.

[0115] C0.05

[0116] Mn0.90

[0117] Al0.06

[0118] Ti0.09

[0119] Nb0.037

[0120] Si0.30

[0121] The total percentage of other elements is less than 0.2% by weight, and wherein Cr is 0.03%, Mo is 0.005%, and W is <0.001%. No impurities exceed the levels specified in the claims.

[0122] The billet is reheated to 1245°C for 25 minutes, then hot-rolled into strip. The finishing temperature is 930°C. The hot-rolled strip is coiled at a coiling temperature of 540°C. The hot-rolled strip is pickled in HCl. Then, the strip is cold-rolled in a five-stand cold rolling mill with a reduction of 35%.

[0123] The cold-rolled strip is then subjected to final annealing in a continuous annealing line (CAL). The final annealing cycle consists of heating to a final annealing temperature of 760°C and holding for 130 seconds. The final-annealed strip is then rapidly cooled to an over-aging temperature of 400°C at a cooling rate of 15°C / s. The strip is then leveled with a rolling elongation of 0.4%.

[0124] The mechanical properties were determined according to the standards presented above under the heading "Mechanical Properties". The results, along with the target values ​​for each mechanical parameter, are shown in Table 1. As can be seen from the table, all target values ​​were achieved.

[0125] Table 1

[0126]

[0127] The microstructure was examined under a scanning electron microscope (SEM) at 2000x magnification. The microstructure was determined to be ≥95% ferrite and <5% pearlite, cementite, carbides, nitrides and / or carbonitrides.

[0128] Example 2

[0129] Steels with the same composition as in Example 1 were tested at different cold rolling degrees and different final annealing temperatures.

[0130] The billet of the composition of Example 1 was reheated to 1245°C for 25 minutes and then hot-rolled into strip. The hot-rolling finishing temperature was 930°C. The hot-rolled strip was coiled at a coiling temperature of 540°C. The hot-rolled strip was pickled in HCl. Then, the strip was cold-rolled in a five-stand cold rolling mill at cold reductions of 25%, 50%, and 75%, respectively.

[0131] The cold-rolled strip is then subjected to final annealing in a continuous annealing line (CAL). The final annealing cycle consists of heating to a final annealing temperature of 700-800°C and holding for 110 seconds. The final-annealed strip is then rapidly cooled to an over-aging temperature of 400°C at a cooling rate of 20°C / s. The strip is then leveled with a rolling elongation of 0.3%.

[0132] Figure 1 The test results are shown. In the figure, it can be seen that the yield strength of the strip subjected to 75% cold reduction moves very rapidly through the desired yield strength range of 800-950 MPa. The yield strength at the final annealing temperature of 720°C is slightly higher than the target range, and the yield strength at 740°C is slightly lower than the target range. Furthermore, the difference ΔR between the yield strength at the final annealing temperature of 700°C and at 800°C respectively... p0.2 Up to 600 MPa. These factors make the results sensitive to process variations.

[0133] The yield strength of strip subjected to a 50% cold reduction is not very sensitive to process variations. Here, the yield strength at a final annealing temperature of 740°C is slightly higher than the target range, and the yield strength at 780°C is slightly lower than the target range. That is, the temperature range that meets the target range is doubled compared to a 75% cold reduction. The difference ΔR between the yield strength at a final annealing temperature of 700°C and 800°C respectively is... p0.2 The pressure has been reduced to 400 MPa. These factors make a 50% cold reduction less sensitive to process changes than a 75% cold reduction. This is still not considered sufficient.

[0134] The yield strength of strip subjected to a 25% cold reduction exhibits minimal sensitivity to process variations. Here, the yield strength at a final annealing temperature of 700°C is within the target range, while the yield strength at 780°C is slightly lower. That is, the temperature range satisfying the target range is doubled compared to a 50% cold reduction. The difference ΔR between the yield strength at a final annealing temperature of 700°C and at 800°C is significant. p0.2 The pressure has been reduced to 200 MPa. These factors make the result of 25% cold reduction the least sensitive to process changes in the cold reduction compared to the comparison.

[0135] Table 2

[0136]

[0137] Example 3

[0138] The 25% cold-reduction steel from Example 2 was compared with the 35% cold-reduction steel. Other processing conditions were the same as in Example 2, except that there was no sample of the 35% cold-reduction steel that was finally annealed at 700°C.

[0139] The comparison results between 25% and 35% cold reduction can be found in Figure 2 As seen in the data, within the target yield strength range of 800-950 MPa, at a temperature range of approximately 70°C, the processing window is largest for a 25% cold reduction. A 35% cold reduction has a narrower processing window of approximately 50°C within the target yield strength range. Both reductions are considered to provide sufficient process stability for the final annealing.

[0140] Example 4

[0141] The 35% cold-reduction steel of Example 3 was compared with two 35% cold-reduction steels that were finally annealed at 50 s and 150 s respectively. Other processing conditions were the same as in Example 2. The difference was that no sample was finally annealed at 700°C. The results are shown in... Figure 3 middle.

[0142] Figure 3 This illustrates how the final annealing time can be used to affect the yield strength at a given cold reduction at different final annealing temperatures. If the yield strength is lower than the target yield strength, the final annealing time can be shortened. This can be seen in the data point at 800°C, where a final annealing time of 50 s is within the target yield strength range, while 110 s and 150 s are below this range. Similarly, if the yield strength is higher, the final annealing time can be lengthened. This can be seen in the data point at 740°C, where a final annealing time of 50 s is outside the target yield strength range, while 110 s and 150 s are within the range.

[0143] Example 5

[0144] This embodiment was conducted to evaluate the effect of different cooling rates in continuous annealing furnaces and batch annealing furnaces on the enlargement ratio (HER). Steel strip was produced as in Example 1 until the final annealing stage.

[0145] The strip was divided into two groups (1) and (2). One group was used for continuous annealing, and the other group was used for batch annealing.

[0146] The first group (1) undergoes final annealing in a continuous annealing line (CAL). The final annealing cycle consists of heating to a final annealing temperature of 740-770°C for 90-150 seconds. The final annealed strip is then rapidly cooled to an over-aging temperature of 400°C at a cooling rate of 15-25°C / s. The strip is then leveled with a rolling elongation of 0.3%.

[0147] The second group (2) is finally annealed in a coiled state in a batch annealing furnace. The annealing cycle includes heating to a final annealing temperature of 600-630°C for 2-15 hours. The finally annealed strip is slowly cooled to room temperature at a cooling rate of 30°C / h. Then the strip is leveled and rolled with a rolling elongation of 0.3%.

[0148] The results show Figure 4 The HER of group (1) which was continuously annealed and rapidly cooled ranged from 62 to 81, with an average of 72. The HER of group (2) which was batch annealed and slowly cooled ranged from 38 to 55, with an average of 46. Therefore, it can be seen that the continuously annealed strip has a significantly higher HER than the batch annealed strip.

[0149] Example 6

[0150] The 35% cold-reduction steel of Example 3 was also studied, with and without over-aging treatment. The results are shown in... Figure 5 middle.

[0151] This comparison shows the yield strength at different annealing temperatures, but with a holding time (tan) of 110 s. For this alloy, a bulk / complete precipitation hardening effect occurs during annealing above 700 °C. Interstitial elements (C, N) precipitate as stable carbides, nitrides, and / or carbonitrides, or form pearlite or cementite during cooling. For this reason, overaging treatment at temperatures below 500 °C no longer has any beneficial or negative strength-increasing effect. Therefore, an overaging step may be performed optionally.

[0152] Example 7

[0153] This embodiment was conducted to evaluate the effect of different annealing temperatures and cold reductions in a continuous annealing line on total elongation.

[0154] Steels with the same composition as in Example 1 were tested at different cold rolling degrees and different final annealing temperatures.

[0155] The billet of the composition of Example 1 was reheated to 1245°C for 25 minutes and then hot-rolled into strip. The hot-rolling finishing temperature was 930°C. The hot-rolled strip was coiled at a coiling temperature of 540°C. The hot-rolled strip was pickled in HCl. Then, the strip was cold-rolled in a five-stand cold rolling mill at cold reductions of 25%, 50%, and 75%, respectively.

[0156] The cold-rolled strip is then subjected to final annealing in a continuous annealing line (CAL). The final annealing cycle consists of heating to a final annealing temperature of 700-800°C and holding for 110 seconds. The final-annealed strip is then rapidly cooled to an over-aging temperature of 400°C at a cooling rate of 20°C / s. The strip is then leveled with a rolling elongation of 0.3%.

[0157] like Figure 6 As shown, the sample with only a 25% cold reduction achieved a minimum total elongation of 9% within a temperature range of 700-800°C. As the degree of cold rolling increases, the strength of the material also increases, which negatively impacts the total elongation. Therefore, the required minimum elongation of 9% can only be achieved through a low degree of cold rolling. These results support the requirement that the cold reduction of the steel used in this invention should be in the range of 20-40%, more preferably 25-35%.

[0158] Industrial applicability

[0159] The steel can be used in applications where high strength is combined with good local formability. One example of such an application is a seat rail.

Claims

1. Cold-rolled steel strip or sheet, having the following characteristics: a) Composition consisting of the following elements, expressed as a percentage by weight: C0.02–0.10 Si 0.05–0.5 Mn0.6–1.0 Al0.015–1.5 Ti 0.03–0.12 Nb 0.01–0.06 Ti+Nb0.05–0.15 The balance consists of iron and impurities. The impurities mentioned are limited to, in weight percent: V≤0.10 Cr≤0.10 Mo≤0.05 W≤0.05 Ni≤0.20 Cu≤0.20 Sn≤0.015 Zr≤0.010 As≤0.010 B≤0.001 Ca≤0.05 P≤0.02 S≤0.005 N≤0.05 O≤0.0003 H≤0.0020 b) Mechanical properties that meet the following conditions according to industrial standard DIN EN ISO 6892-1, wherein the sample is taken in the longitudinal direction of the strip: Yield strength R p0.2 800-950MPa Tensile strength R m 830-1000MPa Total elongation A 80 ≥9% c) Pore expansion ratio λ determined by pore expansion test according to ISO / WD 16630:2009(E): Pore ​​expansion ratio λ ≥ 60% d) Microstructure, by volume%, the microstructure consists of the following: Ferrite ≥95%, and Pearlite, cementite, carbides Nitrogen compounds and / or carbonitrides <5% e) According to JIS Z2248, the bendability Ri / t satisfies: Flexibility Ri / t ≤ 1.0 Where Ri is the ultimate bending radius, defined as the minimum bending radius without cracking, and t is the sheet thickness, and f) Carbon equivalent, in weight %: C Eq =C+Mn / 6+(Cu+Ni) / 15+(Cr+Mo+V) / 5≤0.45。 2. The strip or sheet according to any one of the preceding claims, wherein the carbon equivalent is, in weight %: C Eq =C+Mn / 6+(Cu+Ni) / 15+(Cr+Mo+V) / 5≤0.28。 3. A method for manufacturing cold-rolled steel strip or sheet according to any one of the preceding claims, comprising the following steps: a) Manufacturing a steel billet having the composition according to any one of the preceding claims. b) Reheat the billet to 1200°C to 1300°C and maintain for 10-300 minutes. c) Hot-rolled and reheated billets entirely within the austenitic range, wherein the final hot rolling temperature is in the range of 850-950℃, to obtain hot-rolled steel strip. d) Cool the hot-rolled strip to the coiling temperature. e) Winding hot-rolled strip at a winding temperature within the range of 470-670℃. f) Optionally subject the wound strip to an oxide scale removal process, such as pickling. g) Cold-roll the steel strip with a reduction of 20-40%. h) Final continuous annealing of cold-rolled strip at a temperature ranging from 700 to 800°C for a duration ranging from 25 to 175 seconds. i) Cool the final annealed strip at a cooling rate of 2-100℃ / s. j) Optionally, the final annealed strip is over-aged at 200-500℃ for a duration of 10-1000s. k) Optionally, the strip is leveled by rolling with a rolling elongation of 0-2%. l) Optionally, the strip is coated with a zinc-based coating, and m) Optionally, the strip is cut into sheets.

Citation Information

Patent Citations

  • 700MPa low-alloy and high-strength cold-rolled steel plate for automobile, and preparation method

    CN112680655A

  • Method for producing high-strength cold-formed steel products from a hot rolled strip, said products exhibiting good malleability

    EP1399598B2

  • High-strength cold-rolled low alloy strip steel suitable for bending forming and manufacturing method thereof

    CN109207842A